Rediseño de unidad de educación básica implementando técnicas de construcción ancestral, en la zona rural Isla Puná - Albán Hidalgo, Ariana Gabriela (2024)
Education has, for many years, stood as one of the fundamental pillars for the social and intellectual development of individuals. Consequently, educational institutions emerge as the essential means or support required to furnish individuals with a quality education. The proposal for the "Redesign of Basic Education Unit implementing ancestral construction techniques in the rural area of Isla Puná" originated due to the urgency to address social and economic disparities present in rural areas. The primary focus of this proposal is directed towards the development of first-rate infrastructures, facilitating access to essential services and generating educational opportunities. Essentially, the proposal aims to enhance not only educational but also living conditions on the island, promoting social equity and empowering the community to actively participate in its own progress, thereby contributing to the construction of more just societies..........